Sir Roy Calne: a renaissance man of modern medicine - Baquerizo, Angeles; Jamieson, Neville; Friend, Peter (Frontiers in Transplantation, 2026)
It is a challenging task to encapsulate the prolific life and accomplishments of Sir Roy Calne, a unique individual and pioneer who transformed the impossible into clinical reality, forging a new era of organ transplantation. In the annals of medical history, few figures embody the intersection of science and humanity as did Sir Roy Calne. A pioneering transplant surgeon, scientist, accomplished artist, visionary leader, and devoted family man, Calne's multifaceted legacy continues to influence both medical science and the arts, demonstrating how these two fields can intersect to advance human understanding and compassion. Sir Roy Calne died peacefully in Cambridge on January 6, 2024, leaving behind a legacy that continues to define the field of transplantation.